The Disclosure of petrified unrest: The Gezi protests from the perspective of Jean-Luc Nancy and Walter Benjamin - Kelekçi, Özge. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
Just before and deep down in the Second World War, Walter Benjamin pronounces that progress idea is a conglomeration of catastrophes which always already left traces of who had died, who had been defeated whereas in the illusional idea of progress there exists only the victorious ones. Benjamin manifests that the contradiction of repetitive catastrophes and progress would be revealed only through a dialectical critique which is to read images, objects, commodities, stories of what was historically declared as not having the capacity of juxtaposition. Real History is to start by the help of dialectical critique only and only after the illusion of progress radically halted and the creation of a real state of exception. For Jean-Luc Nancy, relations of human beings, technology and nature that have been agglomerated by the process of globalization is rendered possible only through attribution of an essence to every single being, ever group, every society, every historical period in order to stabilize their place on the earth. Nevertheless, according to Nancy being can never be in an absolutely singular modality, being is always already plural. Humanity is in a prison of globalization that envelops all spacings of freedom. Nancy declares that freedom is to be rendered possible only in the case that they open themselves as singular plurals. In this thesis, Gezi Protests are to be examined by the combining function of Nancy’s idea of the conditions under which a creation of the world through spacing of singular plurals is possible and Benjamin’s methodology of dialectical montage/juxtaposition.